Deontological tradition and the ancient philosophy - Matviychuk, Andriy (Skhid, 2013)
The author considers the formation of deontological tradition in times of ancient philosophy. The work shows the peculiarities involving deontological approach by ancient philosophers. The author outlines the possibilities of developments deontological tradition to justify a new discipline - ecological deontology.